2022
DOI: 10.4102/hts.v78i1.7405
|View full text |Cite
|
Sign up to set email alerts
|

Relation of religion and practical politics: Contextual adoption of constitutional Islamic jurisprudence for Muslim clerics in Indonesia

Abstract: Some clerics (ulama) in the Islamic world are of the view that practical politics is closely related to Islam, which regulates how an order of state is run. This view historically departs from Islamic constitutional jurisprudence texts that justify political Islam. Likewise, some Islamic boarding schools’ (pesantren) clerics, better known as kyai in Indonesia, are of the view that practical politics is not only a world affair but also an activity based on the application of Islamic legal principles in achievin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…There prevails a dialectical mechanism in the pesantren's internal to prevent radicalism in the pesantren, both discursive and practical. The dialectic of radicalism and anti-radicalism in pesantren shows that with the perspective of the Hegelian dialectic theory, the existence of radicalism in pesantren automatically indicates the presence of anti-radicalism (Kusmanto, Fauzi and Jamil, 2015;Yahya and Sahidin, 2022).…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There prevails a dialectical mechanism in the pesantren's internal to prevent radicalism in the pesantren, both discursive and practical. The dialectic of radicalism and anti-radicalism in pesantren shows that with the perspective of the Hegelian dialectic theory, the existence of radicalism in pesantren automatically indicates the presence of anti-radicalism (Kusmanto, Fauzi and Jamil, 2015;Yahya and Sahidin, 2022).…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Several studies have shown increased religious revivalism and radicalism in Southeast Asia (Manurnoor, 2009), including Indonesia. This tendency is manifested in the form of political Islam displayed by revivalist and radical social and religious organizations, such as the Islamic Defenders Front (FPI), the Indonesian Mujahidin Council (MMI), Hizbut-Tahrir Indonesia (HTI) (Shadi, 2017), Laskar Jihad (Asghar, 2015;Santosa and Sjuhro, 2019;Yahya and Sahidin, 2022), and Jama'ah Tabligh (Ma'mun, 2019). Radicalism is a worrying phenomenon in Indonesia (Misbah, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia's open and tolerant culture, forming their identity and tradition rooted in local wisdom, where values of simplicity, openness, and communal living are esteemed (Assa'idi, 2021). This tradition has been substantiated through the extensive historical journey of pesantren within the social, national, and state life (Roqib, 2021;Yahya & Sahidin, 2022).…”
Section: Introductionmentioning
confidence: 99%